Spreadsheet tools for engineers using Excel - Gottfried, Byron S. (McGraw-Hill, 2007)
This book consists of the following many chapters includes: Engineering analysis and spreadsheets, creating an excel worksheet, editing an excel worksheet, graphing data, organizing data, transferring data, engineering applications, converting units, analyzing data statistically, fitting equations to data, solving single equations...